PENANAMAN SIKAP PEDULI LINGKUNGAN PADA SISWA SMP MELALUI KREATIVITAS MENULIS PUISI - Sarwiji Suwandi; Chafit Ulya (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
Nowadays, some disasters hit the Indonesia cause a big loss from society. One of the disaster factors that is the human activity. Public awareness about the important of caring environment isnt growing well yet. So, need the implantation of environment-caring character, especially to the student. One of the ways that is training program of writing poem based on environment-caring to the student of State Junior High School in Surakarta. The efforts were intended to increasing the ecological literacy competence using training program of writing poem based on environment-caring to the student of State Junior High School in Surakarta. This research is a part of the program devotion to the community. Subject of this research are the students in SMPN 15 Surakarta and SMPN 17 Surakarta, the teachers of Indonesian language subject, and the core of MGMP Indonesian Language forum in Surakarta city. This program doing by three phase that are planning, implementation, and evaluation. Result from this program, that is training program of writing poem can increasing the environment-caring character of the student from State Junior High School in Surakarta. Increasing the environment-caring character can be proved through the idea have been formulate on the poem have been written. Increasing the environment-caring character of student on their poem can be classified on four category, that are 1) Caring character towards local environment; 2) Caring character against nature and abiotic factors; 3) Caring character towards plants and herbs; and 4)Concern for the environmental pollution.